What is the underlying structure of the climate, conflict, and socio-economic system in Uganda? A network analysis - Basel, Ashleigh Megan; Onivola Minoarivelo, Henintsoa; Craparo, Alessandro Carmelo William; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Uganda, using network analysis. Results show that, with the Ugandan economy heavily reliant on subsistance agriculture, the network indicates the second cropping season is the most vulerable, leading to poverty risks and conflict